Sticky Prices and Monetary Policy: Evidence from Disaggregated US Data - Boivin, Jean; Giannoni, Marc P; Mihov, Ilian (American Economic Review, 2009)
This paper shows that the recent evidence that disaggregated prices are volatile does not necessarily challenge the hypothesis of price rigidity used in a large class of macroeconomic models. We document the effect of macroeconomic and sectoral disturbances by estimating a factor-augmented vector autoregression using a large set of macroeconomic indicators and disaggregated prices. Our main finding is that disaggregated prices appear sticky in response to macroeconomic and monetary disturbances, but flexible in response to sector-specific shocks. The observed flexibility of disaggregated prices reflects the fact that sector-specific shocks account on average for 85 percent of their monthly fluctuations. (JEL E13, E31, E32, E52)